2004
DOI: 10.1523/jneurosci.1622-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Amygdala Administration of Polyamines Modulates Fear Conditioning in Rats

Abstract: Amygdalar NMDA receptor activation has been implicated in the acquisition of fear memories in rats. However, little is known about the role of endogenous modulators of the NMDA receptor, such as polyamines, in pavlovian fear-conditioning learning. Therefore, in the present study we investigated whether the immediate pretraining or post-training bilateral infusion of arcaine, an antagonist of the NMDA receptor polyamine-binding site, or spermidine, an agonist of the NMDA receptor polyamine-binding site, into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 58 publications
(57 reference statements)
3
48
0
Order By: Relevance
“…Accumulating evidence have also suggested that arcaine impairs memory and prevents the promnestic effect of spermidine (Camera et al 2007;Rubin et al 2000Rubin et al , 2001Rubin et al , 2004, a putative positive modulator of the polyamine binding site at the NMDA receptor. Therefore, considering these studies, it is not surprising that arcaine makes the recall of a task statedependent and transfers the response to MK-801, a classic noncompetitive NMDA receptor antagonist.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Accumulating evidence have also suggested that arcaine impairs memory and prevents the promnestic effect of spermidine (Camera et al 2007;Rubin et al 2000Rubin et al , 2001Rubin et al , 2004, a putative positive modulator of the polyamine binding site at the NMDA receptor. Therefore, considering these studies, it is not surprising that arcaine makes the recall of a task statedependent and transfers the response to MK-801, a classic noncompetitive NMDA receptor antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…Polyamines have also biphasic effects on learning and memory, since they facilitate the acquisition and/or early consolidation of inhibitory avoidance (Berlese et al 2005;Guerra et al 2006;Rubin et al 2000Rubin et al , 2001, fear conditioning (Camera et al 2007;Rubin et al 2004) and the 14-unit Tmaze (Shimada et al 1994) tasks at low doses, but have no effect at high doses. Interestingly, spermidine has no effect on late consolidation and retrieval (Berlese et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the conditioning trial, each animal was subjected to a single fear conditioning training session, as described by Rubin et al (2004) with some modifications. In brief, the rat was placed in the conditioning chamber (conditioned stimulus, CS) and habituated to the apparatus for 3 min.…”
Section: Contextual Fear Conditioningmentioning
confidence: 99%